If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = 4a + -1 Reorder the terms: 3 + 6x = 4a + -1 Reorder the terms: 3 + 6x = -1 + 4a Solving 3 + 6x = -1 + 4a Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6x = -1 + -3 + 4a Combine like terms: 3 + -3 = 0 0 + 6x = -1 + -3 + 4a 6x = -1 + -3 + 4a Combine like terms: -1 + -3 = -4 6x = -4 + 4a Divide each side by '6'. x = -0.6666666667 + 0.6666666667a Simplifying x = -0.6666666667 + 0.6666666667a
| 2n-6=4n+24 | | 2(x-4)+x=-9(5-x) | | 3x1/5= | | 36c^2-(a^2+14ab+49b^2)=0 | | 8x+9-3x+12=14-7x | | N/2=30/10 | | v^2-7v-12=0 | | 2(n-6)+n=-36 | | 7x+4+7x+4-4+(7x+4)2=180 | | (1=7i)/(-5-i) | | 1/(-5-i) | | 3=-2a+7 | | 7/3z-1/4=5 | | x+1.5-0.5x=45 | | -2(y+3)+8=4y-2 | | 4(2y-8)-3y=-17 | | 2x-1=100 | | 85.5=9(m+3.2) | | 3(x-2)+1=2+4x | | 3/3v | | 4(x-3)=-8(x+1) | | s/13=4 | | [-1,2],y=1/2x-3 | | 45+x=x | | -19=6w+4w | | -19-1m=8(1+1m) | | -2(3a+5)=-46 | | -5(3u-4)+6u=3(u+8) | | 9/7=z/2 | | 10-x+7=20 | | 3/14(6/13) | | 7-8=13 |